Zoning in reunified Berlin - Gabriel M. Ahlfeldt; Wolfgang Maennig; Felix J. Richter (University of Hamburg, Faculty of Business, Economics and Social Sciences, Chair for Economic Policy, 2017)
While urban renewal programs have become widely used policy measures to target urban devel-opment less is known about the reasons why certain areas are more responsive to policy inter-ventions than others. With this study we address some of these issues by analyzing an urban re-newal program in Berlin, Germany, with 22 designated renewal zones between 1990 and 2012. We separately estimate the effects of the renewal policy on property prices for each respective redevelopment area by comparing price developments in these areas to a series of runner-up areas and to geographically close transactions. We find a considerable amount of heterogeneity. While some areas profit form the renewal policies, there are several areas which develop quite differently and end up with a decrease in property prices due to the urban renewal policy.
Keywords: D62; H23; R21; R31; 330; Urban; renewal; revitalization; area level; hedonic; policy evaluation